Perkembangan Pendidikan Islam Berbasis Kearifan Lokal Budaya Samin Di Lembaga Pendidikan Ma’arif Kabupaten Blora - Ghofiqi, Mohammad Imam Mudi Al (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The aim of this research is the implementation of an Islamic education curriculum based on local wisdom and efforts to instill Islamic values ​​based on local wisdom in educational practice. The design of this research is a Literature Review or literature review. The research results show that 1) the implementation of the independent learning concept is designed so that students have many alternative competencies and relevant skills to be developed in the future. developed based on understanding and practicing the values ​​of monotheism radically (deeply rooted). Efforts to instill Islamic education values ​​in local wisdom are carried out through Islamic education values ​​in local wisdom which have been instilled through religious cultivation methods in the form of faith values, worship values, moral values ​​by combining Islamic religious habits in the free learning education curriculum.